2020
DOI: 10.12968/jowc.2020.29.3.162
|View full text |Cite
|
Sign up to set email alerts
|

Use of a TLC-Ag dressing on 2270 patients with wounds at risk or with signs of local infection: an observational study

Abstract: Objective: A description of wounds treated with a poly-absorbent silver dressing (with technology lipido-colloid with silver ions, TLC-Ag), and evaluation of the short-term clinical impact of the dressing on the wound healing process, under real-life conditions. Method: A large, prospective, multicentre, observational study of patients in 81 centres in Germany, presenting with an exuding wound at risk or with clinical signs of local infection for whom the evaluated TLC-Ag dressing (UrgoClean Ag, Laboratoires U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Therefore, reducing the use of antibiotics and finding an effective alternative are important for clinical practice. Ag is an attractive alternative to antibiotics because of its excellent property against a wide range of pathogens (Zheng et al, 2019) and has been widely used in medical products, such as wounds dressing and catheters, to inhibit the bacteria growth (Rtimi et al, 2016;Dissemond et al, 2020). As shown in Figures 3A,B, GT/PCL groups with Ag (including GT/PCL-Ag and GT/PCL-Ag-Mg membranes) significantly inhibited the growth of E. coli and S. aureus.…”
Section: Antibacterial Functionmentioning
confidence: 97%
“…Therefore, reducing the use of antibiotics and finding an effective alternative are important for clinical practice. Ag is an attractive alternative to antibiotics because of its excellent property against a wide range of pathogens (Zheng et al, 2019) and has been widely used in medical products, such as wounds dressing and catheters, to inhibit the bacteria growth (Rtimi et al, 2016;Dissemond et al, 2020). As shown in Figures 3A,B, GT/PCL groups with Ag (including GT/PCL-Ag and GT/PCL-Ag-Mg membranes) significantly inhibited the growth of E. coli and S. aureus.…”
Section: Antibacterial Functionmentioning
confidence: 97%
“…Other varieties of silver dressings have also been reported in treating skin breakdown in preterm infants and have achieved a good effect[ 25 , 26 ]. According to the manufacturer’s instructions, it is recommended to change dressings as often as required, at least once 1 wk, depending on the clinical status of the wound and exudate volume[ 27 ]. Some scholars have suggested that silver dressing use should be limited to no longer than 2 consecutive weeks because of silver toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The therapy and prevention of wound infections with antiseptics have a high priority in modern therapeutic concepts due to the development of antibiotic resistance, the risks of allergic and anaphylactic side-effects with topical antibiotic application, and the availability of highly effective antiseptics with good tolerability. [17][18][19] Various treatment options are available for antiseptic wound therapy. 20 Whenever possible, the systemic administration of antibiotics should be avoided or should be used for the detection of systemic infections only.…”
Section: Discussionmentioning
confidence: 99%